PKM Pelatihan Bimbingan Karir Pencegahan Anak Putus Sekolah pada Kelompok Guru BK di Kabupaten Sidrap - Abdullah Sinring; Nur Fadhilah Umar (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. Based on the results of the FGD and interviews with BK teachers and students in Turikale sub-district, information was obtained that training related to career guidance for BK teachers at SMP / Mts to prevent children from dropping out of school was still very low. In addition, the results of interviews with counseling teachers show that 52% of BK services are dominated by tutoring, 35% for personal-social services and 12% for career guidance services. The results of interviews with counseling teachers obtained information that the implementation of career guidance only uses the lecture method in all situations without paying attention to students and the material given. As a result, students tend to neglect following career guidance and have low career expectations in the future. Based on the above background, it is deemed necessary to provide career guidance training for BK teachers at SMP / Mts in order to prevent children from dropping out of school. The implementation of this PKM is carried out by adopting action research steps consisting of 5 stages, namely: planning, action, observation, evaluation and reflection and mentoring. This training activity will be carried out for 4 days of this activity, and will be given assistance after the activity for 3 months. The target participants in this activity are 40 BK teachers. There are several outputs that will be produced through this program, namely 1) Scientific Publications in the Journal